E-government implementation in the Kingdom of Saudi Arabia: an exploratory study on current practices, obstacles and challenges - Basamh, Saeed Saleem; Qudaih, Hani A.; Suhaimi, Mohd Adam (Centre for Promoting Ideas, USA, 2014)
The concept of electronic government (e-government) is to utilize Information and Communication Technology (ICT) to deliver government services. Governments around the world are adopting and improving e-government to reduce costs, improve services, save time and increase effectiveness and efficiency in a public sector. Therefore, the Saudi government is considering e-government as a top priority. The Government of Saudi Arabia attaches high significance to the e-government concept and the transformation process that leads to its realization. This study will explore the adoption and implementation of e-government thoroughly to address the current practices, and to identify challenges and obstacles that affect the improvements in the e-services provided from a society perspective. An intensive literature study on the subject matter will help revealing the state of egovernment services towards the future. At the end, numbers of recommendations to the successful adoption of egovernment services in the Kingdom of Saudi Arabia are mentioned after addressing the problems.